Analisis Kemampuan Berpikir Aljabar Peserta Didik SMP dalam Menyelesaikan Soal Generalisasi Pola - Saiful Fadli; Lalu Ajimuliardi Akbar; Fatimatus Solihah; Helmi Rahmawati; Vianda Sulistia (MAN 4 Kota Pekanbaru, 2026)
Algebraic thinking is crucial for assisting students in the mathematics learning process. Algebraic thinking is the process by which students solve problems, identify problems, and present them mathematically in mathematics learning. Generalization is part of algebraic thinking and is an essential component of the educational curriculum. However, there are several obstacles and challenges in students' algebraic thinking, particularly in generalizing patterns. Therefore, the purpose of this study was to analyze junior high school students' algebraic thinking skills in solving pattern generalization problems. This study is a descriptive qualitative study, where the results are in the form of descriptions of students' algebraic thinking skills. The results of this study indicate that subjects with high-level algebraic thinking skills tend to generalize factually and symbolically, and the data fulfills all indicators of algebraic thinking. Subjects with moderate algebraic thinking skills only tend to generalize factually and only fulfill some algebraic thinking skills. Subjects with low algebraic skills tend to have difficulty generalizing patterns and only fulfill a few algebraic thinking skills.